Cellular metabolism hijacked by viruses for immunoevasion: potential antiviral targets - Li, Jiaqi; Wang, Yanjin; Deng, Hao; Li, Su; Qiu, Hua-Ji (Frontiers in Immunology, 2023)
Cellular metabolism plays a central role in the regulation of both innate and adaptive immunity. Immune cells utilize metabolic pathways to modulate the cellular differentiation or death. The intricate interplay between metabolism and immune response is critical for maintaining homeostasis and effective antiviral activities. In recent years, immunometabolism induced by viral infections has been extensively investigated, and accumulating evidence has indicated that cellular metabolism can be hijacked to facilitate viral replication. Generally, virus-induced changes in cellular metabolism lead to the reprogramming of metabolites and metabolic enzymes in different pathways (glucose, lipid, and amino acid metabolism). Metabolic reprogramming affects 2 the function of immune cells, regulates the expression of immune molecules and determines cell fate. Therefore, it is important to explore the effector molecules with immunomodulatory properties, including metabolites, metabolic enzymes, and other immunometabolism-related molecules as the antivirals. This review summarizes the relevant advances in the field of metabolic reprogramming induced by viral infections, providing novel insights for the development of antivirals.